PENERAPAN METODE WASPAS UNTUK MENENTUKAN PENERIMA BEASISWA PADA PERGURUAN TINGGI NEGERI - ihsan, Khairul; Ginting, Guidio Leonarde (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Determination of recipients of Mou scholarships at the Labuhan Batu Utara Regent's Office is done by selecting students who take a series of given test stages and appropriate criteria. The problem faced by the selection team is how to determine outstanding students from a number of alternatives that have their respective strengths and weaknesses so that they are not well targeted in providing the best value to be analyzed. This system is a Decision Support System (SPK) which was built using the WASPAS method and designed using Microsoft Visual Studio 2008 and using a Microsoft Access database. Data processing will be carried out by the Selection Team from the Labuhan Batu Utara Regent's Office by entering the value data of the prospective scholarship recipients, the system will perform calculations according to the WASPAS principle which ultimately results in a ranking that can help the selection team compare the rankings obtained. The system created has been able to determine students who are entitled to receive scholarships.